PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN KOPERASI KPRI “DIAN HUSADA” KABUPATEN DEMAK - Luhgiatno, Luhgiatno; Adhi, Daniel Kartika; Wahyuningsih, Panca (Fokus ABDIMAS, 2022)
One of the concrete efforts to realize transparency and accountability of the entity's financial management is the submission of an entity's financial accountability report that meets the principles on time and is prepared by following applicable financial accounting standards. Financial statements show the performance of entities that can be used by internal and external parties in making decisions. The Civil Service Cooperative of the Republic of Indonesia (KPRI) is a cooperative established and managed for the benefit of Civil Servants. KPRI Dian Husada as one of the economic nandi veins on a micro scale needs assistance in terms of managing and preparing financial statement reporting, considering that there are still many entities that do not understand the Financial Accounting Standards (SAK) ETAP in preparing financial statements. Service activities to assist the preparation of financial statements at KPRI Dian Husada are carried out with a qualitative method approach. There are three methods of data collection in this service, namely; interviews, observations, and analysis of documents. From the results of mentoring and preparing financial statements, KPRI "Dian Husada" was assisted in preparing financial statements in accordance with SAK ETAP. Keywords: Mentoring, Preparation, KPRI “Dian Husada”